2009
DOI: 10.1177/0961203309351033
|View full text |Cite
|
Sign up to set email alerts
|

SLE disease patterns in a Danish population-based lupus cohort: an 8-year prospective study

Abstract: In 1995 all systemic lupus erythematosus (SLE) patients in the county of Funen were retrieved from four separate and independent sources as part of an 8-year prospective study to determine the pattern of disease activity and damage accumulation in a community based lupus cohort of predominantly Scandinavian ancestry. Incident cases were subsequently identified by surveillance of these sources. Established and new cases underwent annual, structured interviews, clinical examination and blood sampling. The System… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 29 publications
4
30
0
2
Order By: Relevance
“…It is also worth pointing out that the rate of flares we have observed in our patients is consistent with the rates observed by investigators from Denmark (17 per 100 patient-years),45 Padova, Italy (19 per 100 patient-years)46 and Hong Kong (24 per 100 patient-years),47 but lower that the ones reported from Germany (124 per 100 patient-years),48 and higher than the rates reported in Rome, Italy (7 per 100 patient-years) 49. Other definitions of flares have yielded higher rates of flares (65–194 per 100 patient-years) in patients with lupus.…”
Section: Discussionsupporting
confidence: 93%
“…It is also worth pointing out that the rate of flares we have observed in our patients is consistent with the rates observed by investigators from Denmark (17 per 100 patient-years),45 Padova, Italy (19 per 100 patient-years)46 and Hong Kong (24 per 100 patient-years),47 but lower that the ones reported from Germany (124 per 100 patient-years),48 and higher than the rates reported in Rome, Italy (7 per 100 patient-years) 49. Other definitions of flares have yielded higher rates of flares (65–194 per 100 patient-years) in patients with lupus.…”
Section: Discussionsupporting
confidence: 93%
“…In our cohort, 100% of patients were Caucasian and this could also contribute to the better outcome in terms of remission compared with other studies 8 9 12–15. The exclusion of patients with different ethnicity can partially explain why our patients had a lower prevalence of glomerulonephritis and vasculitis and took a lower cumulative dose of corticosteroids 14 15…”
Section: Discussionmentioning
confidence: 59%
“…The two validation studies of the LDIQ showed mean SDI scores of 1.53 and 1.94 that are comparable to the SDI in our population, as did a Danish population examined by Laustrup et al with an SDI between 1.5 and 2 (disease duration >8 years). 13 16 showed considerably higher or lower SDI values. Therefore our cohort reflects an ordinary patient composition with respect to acquired damage.…”
Section: Discussionmentioning
confidence: 91%